The effect of water-soluble tomato concentrate on elevated serum cholesterol in the middle-aged and elderly Chinese individuals - Yu, Yingxiang; Wu, Yifan; Xie, Lan; Chang, Cuiqing (Frontiers in Nutrition, 2024)
Water-soluble tomato concentrate (WSTC) has demonstrated beneficial effect on blood flow in healthy populations. The prospective, randomized, double-blind, and placebo-controlled clinical trial was conducted to explore the impact of WSTC on individuals with elevated cholesterol levels. Sixty participants aged 35–65 with high cholesterol were enrolled and evenly divided into a treatment group (FFG) and a placebo group (PCG). Over a 60-day period comprising a 45-day treatment phase followed by a 15-day observational follow-up. Participants in the FFG received 300 mg daily of Fruitflow tablets, while the PCG were received placebos. The study showed that there were no significant differences in baseline parameters between the FFG and PCG (p > 0.05). Post-intervention, the FFG exhibited significant reductions in systolic blood pressure (SBP) and diastolic blood pressure (DBP) by 4.2% (SBP, p < 0.001) and 3.8% (DBP, p = 0.015), respectively, compared to the PCG (p = 0.041). These reductions were sustained during the follow-up period. In contrast, the PCG showed no significant changes in SBP and DBP (p > 0.05). Stratified analysis by hypertension status revealed a significant SBP reductions both hypertensive and non-hypertensive FFG subjects (p < 0.05), with a trend towards DBP reduction. No significant changes in SBP and DBP were observed in the PCG. Moreover, the FFG group showed a significant increase in high-density lipoprotein (HDL) cholesterol (p < 0.05), along with a marked reduction in both weight and body mass index (BMI) (p < 0.05). The FFG also showed decreased levels of homocysteine, high-sensitivity C-reactive protein, and fasting blood glucose compared to the PCG (p < 0.05). In conclusion, WSTC has the potential to lower blood pressure and cardiovascular risk profiles in hypercholesterolemic individuals, presenting a viable non-harmacological option for enhancing cardiovascular health. Clinical trial registration: https://www.chictr.org.cn/showproj.html?proj=27052, identifier ChiCTR1800015904.